2016
DOI: 10.1249/mss.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Step Rate on Shin Injury and Anterior Knee Pain in High School Runners

Abstract: A lower running step rate was associated with a greater likelihood of shin injury at both self-selected and fixed running speeds. Future studies evaluating whether increasing running step rate reduces shin injury risk and time lost during a high school cross-country season should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 26 publications
3
68
0
2
Order By: Relevance
“…A prospective study of high school runners found that those who habitually ran with a higher step rate had a reduced likelihood of shin injury 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of high school runners found that those who habitually ran with a higher step rate had a reduced likelihood of shin injury 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Levels of evidence are shown with the following symbols: (double asterisks) limited evidence, (asterisk) very limited evidence, (double tagger) no statistical analysis. A detailed description of all significant outcome measures is provided using following superscripts: a in female runners developing patellofemoral pain, b in female runners developing iliotibial band syndrome, c in a mixed-sex population of experienced runners developing patellofemoral pain, d in a mixed-sex population of crosscountry runners developing an RRI, e in a mixed-sex population of recreational runners developing Achilles tendinopathy, f in a mixedsex population of recreational runners developing an RRI, g in male novice runners developing an RRI, h in female recreational runners who required medical attention compared with female recreational runners who never sustained an RRI before, i in male and female novice runners developing an RRI, j in female recreational runners developing an RRI, k in a mixed-sex population of novice runners developing patellofemoral pain, l in a mixed-sex population of novice runners sustaining an RRI, m in a mixed-sex population of novice runners developing Achilles tendinopathy, n in male runners developing Achilles tendinopathy, plantar fasciopathy and medial tibial stress syndrome, o in a mixed-sex population of cross-country runners developing shin injury [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. MT metatarsal, RRI running-related injury, ↑ greater, ↓ smaller forefoot at forefoot flat (ES = 0.88) [47] in a mixed-sex population of novice runners, while limited evidence indicated a greater medial pressure in recreational male runners developing Achilles tendinopathy, plantar fasciopathy and medial tibial stress syndrome [48].…”
Section: Plantar Pressure Variables Inconsistent Evidencementioning
confidence: 99%
“…Along with the popularity of running, the number of people suffering from running-related injuries has steadily increased (Abt et al, 2011;Fields et al, 2010). In an effort to combat this high level of injuries, there has been increased demand for running gait research and a growing body of evidence has examined the influence of stride characteristics on the risk of injury (e.g., spatiotemporal parameters such as step frequency [SF], step length [SL], and ground contact time [CT]) (Luedke et al, 2016;Schubert et al, 2014). However, the relationship between the spatiotemporal parameters of running and both performance and injury risk still remains unclear.…”
Section: Introductionmentioning
confidence: 99%